Morphology of the larval stages of Macropodia czernjawskii (Brandt, 1880) (Decapoda, Brachyura, Inachidae) reared in the laboratory - Marco-Herrero, Elena; Rodríguez, Antonio; Cuesta, José A. (Zootaxa, 2012)
The complete larval development of Macropodia czernjawskii (Brandt, 1880), is described and illustrated for the firsttime. Larvae were reared in the laboratory and development consisted of two zoeal stages and a megalopa. The main dif-ference in the zoeal stages is the absence of lateral spines on the telson furcae, which allow it to be distinguished from the remaining species of Macropodia as well as from the zoeae of most majoids.